Synthesis Of Large Pore Zeolites For Catalyzing Furanic-Type Fuel Compounds - Ahmad, Nur Hidayahni (2021)
Linde type L (LTL topology) and offretite (OFF topology) zeolites are large pore zeolites (diameter 7.1 × 7.1 Å2 and 6.7 × 6.8 Å2, respectively). The aim of this project is to synthesize and apply LTL and OFF acidic zeolites in catalyzing various furanic-type reactions